Endothelial AGO1 deficiency reduces breast cancer burden in mice - Xuejing Liu; Alonso Tapia; Dongqiang Yuan; Xiaofang Tang; Yingjun Luo; Naseeb Kaur Malhi; Muxi Chen; Kwan Ho Law; Mohamad Haidar; Skylar Giacobetti; Jiawei Sun; Anthony Park; et al. (Angiogenesis, 2026)
Endothelial cells (ECs) are crucial in cancer development and progression, partly by regulating tumor angiogenesis and immune modulation. As a key component of the RNA-induced silencing complex, Argonaute 1 (AGO1) regulates tumor biology, yet the specific function of AGO1 within ECs in the tumor microenvironment remains undefined. Here, we investigated the effects of endothelial-specific AGO1 knockout (EC-AGO1-KO) on tumor vascularization and immune regulation in a mouse syngeneic breast cancer model induced by E0771 cells. EC-AGO1-KO mice exhibited significantly reduced tumor burden compared to their wild-type (WT) littermates, accompanied by reduced vascularization and enhanced immune cell infiltration. Histological and single-cell RNA sequencing analyses revealed increased infiltration of CD8⁺ T cells and macrophages in EC-AGO1-KO tumors, indicative of an immunostimulatory microenvironment. In vitro, AGO1 knockdown in mouse ECs co-cultured with E0771 tumor cells led to higher levels of Cxcl10 and Vcam1 expression, suggesting a pro-inflammatory and leukocyte-recruiting effect. Together, these findings identify endothelial AGO1 as a key regulator of tumor vasculature and immune homeostasis in breast cancer, suggesting that targeting endothelial AGO1 may represent a novel therapeutic strategy to modulate tumor vasculature while enhancing anti-tumor immunity.